Challenges in Teaching English under the Emancipated Curriculum at Elementary Schools - Metty Agustine Primary; Hasan, Evi Kofifah (Language Circle: Journal of Language and Literature, 2025)
The Emancipated Curriculum (Kurikulum Merdeka) was introduced at the beginning of 2022 by the Indonesian Minister of Education, Culture, Research, and Technology, Nadiem Anwar Makarim. The curriculum introduces several differences from the previous curriculum, one of which pertains to Teaching English to Young Learners (TEYL). English lessons have been reintroduced in elementary schools after being absent for some time. However, this change poses challenges for teachers. The absence of specialized English teachers in elementary schools demands that classroom teachers assume the responsibility of teaching English subjects. This study aims to explore the challenges faced by elementary school teachers in teaching English under the emancipated curriculum. Data collection was conducted through semi-structured interviews with two classroom teachers as participants. The obtained data were then analyzed using thematic analysis to uncover the findings. The research was conducted in an elementary school in Ciamis, West Java, Indonesia. The results reveal that elementary school teachers face four main challenges in teaching English under the curriculum. These challenges include a lack of professional development for teachers, teachers’ pedagogical competencies, the characteristics of young learners, and the lack of educational resources. It is recommended that educational authorities implement comprehensive professional development programs to enhance teachers' pedagogical competencies, with a focus on innovative and student-centered approaches that are suitable for young learners. Additionally, increasing the availability of educational resources and providing continuous support for teachers in adapting to the emancipated curriculum will address the identified challenges and improve the quality of English teaching.